Exploring efficiency differences between medical home and non-medical home hospitals. (3rd July 2017) - DePuccio, Matthew J.; Ozcan, Yasar A.
Abstract: Although research on the delivery and effectiveness of medical home care in the outpatient setting is rapidly emerging, little is known about the performance of hospitals claiming to have adopted a medical home model. Exploring the linkages between medical home programs and measures of hospital efficiency is a step towards understanding if this model of care can help stem rising healthcare costs and increase hospital productivity. To explore this relationship this study employed a retrospective, cross-sectional, two-stage approach involving (1) bias-corrected data envelopment analysis (DEA) and (2) Tobit regression. Findings from the DEA suggest that a total of 119 of 2212 U.S. hospitals were technically efficient in 2012. Also, hospitals claiming to have a medical home program were more efficient (0.73) than those reporting not having a medical home program (0.69). The regression model predicts an association between hospitals reporting to have a medical home program and hospital efficiency while controlling for hospital and market characteristics. More research is necessary to determine what proponents of medical home programs are advantageous for improving hospital efficiency, and how programs can be tailored to reduce unnecessary spending while improving the quality of care provided in a hospital setting.